Dividend Policy under Conditions of Capital Market and Signalling Equilibria - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1985)
This study develops a capital market equilibrium model under condition of dividend signaling equilibrium in order to explain why firms pay dividends and what factors can effect the optimal dividend payments. Under the assumption that dividends function as a signal through which the uncertain future cash flow of the firm can be unambiguously revealed to the market, the costs and benefit of paying dividends are investigated from the derived joint capital market/signaling equilibrium model. The costs are found to be the tax penalty on cash dividends, the market moral hazard penalty assessed in the market, and an increase in the covariance risk. The benefit is defined as the increased value of the firm at the end of the period which is signaled by the committed dividends. The optimal dividend function is examined through an optimization process. It is shown that the six factors relevant to the optimal dividend function are the return on a risk-free asset, the return on a zero-beta portfolio, the market moral hazard penalty rates, the variability of future earnings, the weighted average of investors' marginal tax rates, and the covariance risk of the firm's future earnings with the market's expected rates of return. Analysis of the comparative statics shows that all of these six variables have negative effects on the optimal dividend payments. Pooled time series and cross sectional regressions are employed to test these six hypotheses. The empirical results generally support the dividend signaling theory of this study.